2015
DOI: 10.1007/s00520-015-2997-x
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and inflammation are independent predictors of survival in male patients newly diagnosed with small cell lung cancer

Abstract: In SCLC, sarcopenic male patients with high NLR have a poor prognosis and do not tolerate standard treatment. Intensive supportive care is needed in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
100
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 36 publications
9
100
3
Order By: Relevance
“…Furthermore, multivariable regression analysis showed that L1MI was the only independent predictor of L3MI, and using the derived regression equation between L1MI and L3MI, we were able to suggest L1MI cutoffs for sarcopenia. Pectoralis muscle has the merit of being easily demarcated and quantified due to its anatomical features on chest CT images, and furthermore, prognosis was poor in male SCLC patients with a low PMA and an elevated neutrophil-to-lymphocyte ratio [11]. In a recent study [15], a moderate correlation (r = 0.665, p < 0.001) was observed between CT-determined PMA and BIA-determined total body SMM in healthy subjects, and this association remained significant after adjusting for sex, weight, height, and age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, multivariable regression analysis showed that L1MI was the only independent predictor of L3MI, and using the derived regression equation between L1MI and L3MI, we were able to suggest L1MI cutoffs for sarcopenia. Pectoralis muscle has the merit of being easily demarcated and quantified due to its anatomical features on chest CT images, and furthermore, prognosis was poor in male SCLC patients with a low PMA and an elevated neutrophil-to-lymphocyte ratio [11]. In a recent study [15], a moderate correlation (r = 0.665, p < 0.001) was observed between CT-determined PMA and BIA-determined total body SMM in healthy subjects, and this association remained significant after adjusting for sex, weight, height, and age.…”
Section: Discussionmentioning
confidence: 99%
“…Although chest CT is the standard imaging modality used to diagnose and follow up lung cancer, it rarely extends to the L3 level, which precludes its use for assessing the status of sarcopenia in lung cancer patients. For this reason, one study evaluated pectoralis muscle area (PMA) to define sarcopenia in patients with small-cell lung cancer (SCLC) [11]. Although L1 is covered during chest CT examinations and muscle area at the first lumbar vertebra level (L1MA) was found to show a high correlation (r = 0.903, p < 0.001) with total body SMM in healthy subjects [7], the predictive values of chest CT-determined SMM indices for determining sarcopenia have not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing data that malnutrition, skeletal muscle loss, and a systemic inflammatory response are associated with poor outcomes in patients suffering from various types of cancers . We previously reported that skeletal muscle loss was strongly associated with a poor long‐term prognosis in patients who underwent surgical treatment of AEG and UGC .…”
Section: Introductionmentioning
confidence: 96%
“…One study reported that patients with sarcopenia suffered grade 3 or 4 AEs, and another reported that LSMM predicted early dose‐limiting toxicities of treatment with sorafenib . Others have indicated that high anticancer drug exposure in patients with LSMM may be correlated with increased chemotherapy toxicity, leading to early cessation and early progression in renal cell carcinoma, lung cancer, and HCC . Previous studies have reported that the duration of sorafenib treatment is significantly shorter in patients with LSMM than in non‐LSMM patients .…”
Section: Discussionmentioning
confidence: 99%